KEMAMPUAN METAKOGNISI MAHASISWA DALAM MENYELESAIKAN SOAL-SOAL PERSAMAAN DIFFERENSIAL BIASA (Universitas Dr. Soetomo, 2015)
The process of thinking in problem solving is an important thing to get the attention of educators , especially to assist learners in order to develop a better ability to solve problems in the real-world context and in the context of mathematics . This is in line with the opinion Lester ( in Gartman and Freiberg , 1993) that the main purpose of teaching problem solving in mathematics is not just to equip learners with a set of skills or processes, but rather to enable learners to think for himself. The objective of this study was to describe the student metacognitive level in solving problems of ordinary differential equations. These objectives can be revealed if observed in terms of the process. So that the procedure produces descriptive data in the form of words, written or oral obtained from research subjects. For the purposes of in-depth information that can reveal metacognitive level students, it is necessary informant as much as 3 students selected for an interview based on the ranking score of the mathematics of the test results. Preparation of the rankings are divided into three categories, namely one each student with math scored high, medium, and low. The score category classification using the method of determining the position of the student with a standard deviation based on the reference